Press freedom in Nepal: A gap between constitutional provisions and laws - Bidari, Shanta Ram (Nepali Media: Issue of Ethics and Sustainability, 2025)
Press freedom is a cornerstone of democratic governance, yet it remains particularly vulnerable in transitional political contexts. Nepal—marked by its history of monarchical rule, political upheavals, and constitutional shifts—offers a compelling case for examining how media laws both empower and constrain journalistic practice. This article critically analyzes the evolution of Nepal’s media law framework, tracing its development from the Panchayat era to the present democratic republic. It assesses key legal provisions governing freedom of expression, the press, and broadcasting, while identifying structural, political, and institutional challenges that continue to compromise journalistic independence. Drawing on international norms and comparative perspectives, the article explores the tensions between regulation and freedom, the roles of state institutions, and the influence of political and commercial actors. While Nepal’s constitution formally enshrines strong protections for press freedom, the paper argues that vague legislation, weak enforcement, and pervasive political interference undermine these guarantees in practice. The article concludes by offering policy recommendations aimed at strengthening Nepal’s media law landscape and reinforcing press freedom in line with democratic principles and international standards.